Argentine Catholicism during the last military dictatorship: unresolved tensions and tragic outcomes - Catoggio, Maria Soledad (2013)
This paper analyzes the relationships between institutional discipline and state repression whithin the Catholic church in Argentina during the last military dictatorship. Rather than a natural continuity between both terms we find a series of tensions, firmly installed during the sixties and still unresolved at the beginning of the dictatorship, leading to dramatic resolutions. In fact, State terrorism did not appear out of thin air. On the contrary, it exacerbated tensions already existing in the Catholic world. During the decade before the last dictatorship, countless conflicts occurred between ecclesiastical Authorities, the military clergy, and members of the military forces, conflicts whose unresolved nature led to extreme solutions such as, on one hand, the military's attempt to define Catholic ‘orthodoxy’ and, on the other, the clergy's participation in the repressive machinery of the state. At the same time, the decade set the stage for a whole series of confrontations between ecclesiastical authorities and their own clergy members to define conciliar ‘renewal'. These confrontations coexisted with propagandistic accusations of ‘subversion' and ‘infiltration' in the Catholic institution. At the beginning of the 1970s, these accusations gave way to repression. The unresolved tension between institutional discipline and state repression which started in the previous decade eroded the corporative solidarity and enabled vertical and horizontal ruptures within the church. This had tragic consequences during the last dictatorship, which occurred in circumstances that, rather than following a recurrent pattern, were the result of a variety of situations that were unpredictable for the actors.